BETWEEN SCYLLA AND CHARYBDIS (School in a Totalitarian Society) - Dokashenko, Halyna (Професіоналізм педагога: теоретичні й методичні аспекти, 2019)
In the article a rather effective scientific approach is used – the study of totalitarianism through certain spheres of the spiritual life of society, that is the most complex and contradictory sphere of life of the human community. The object of the study is the school education of Bulgaria in the socialist period from the September 1944 events connected with the rise to power of the Patriotic Front Government to the “palace coup” in 1989, when the country’s educators were faced with the choice between deep national traditions of schooling and the unified approaches of the socialist era. The choice of the country is connected with the intention to analyze the situation in education development under the conditions of the Soviet model of the regime other than it was in the USSR, which was called “People’s Democracy”, and to define the peculiarities of this regime in one of the countries of the former “socialist camp”. Among these features it is identified the role of the personal factor in the party – governmental leadership of this Balkan country. The historical and pedagogical process in Bulgaria is characterized by the indicators of several levels. At the general level, it is shown that the education system is an important component and a leading feature of human civilization. The general pattern (that is, an indicator that applies to all or at least the vast majority of states) of the educational space development of Bulgaria in a certain period was a steady trend of increasing the role of education in public progress, when education and upbringing were focused on reaching all the segments of the population. The peculiarities, inherent in particular groups of states, were the features characteristic for the education development in socialist countries: the party leadership and a strict control of party bodies, ideologization of the educational process and extracurricular work, too high degree of planning, the subordination of state structures to party organs, an excessive centralization, etc; the individual features include the preservation of the national system of public-state leadership in the spiritual sphere, the non-antagonistic coexistence of religious and secular-democratic consciousness of an individual and a high role and place of a Bulgarian teacher in the society. Contrary to the totalitarian rule, the Bulgarian teacher patiently taught children and adults to peace, tolerance and sociability, respect for work and social justice. Further explorations of the author will be devoted to the analysis of the common features of the education development in the countries of the Balkan region, which have historically been at the intersection of western and eastern trends, under the influence of multi-vector approaches and orientations.